What is the Problem with Stabilization Clauses in Petroleum Agreements? - Nalule, Victoria R. (Journal of Sustainable Development Law and Policy, 2025)
International Oil Companies (IOCs) continue to invest in countries which do not have stabilization clauses. Why is this so? What is the essence of these clauses? One of the curiosities of stabilization clauses in petroleum agreements, is that most developed countries will not offer them to investors. So, why do developing countries with stable political, fiscal and regulatory climate offer them? Additionally, history shows that these stabilization clauses have not deterred host governments from expropriating petroleum investments. While governments may be able to make commitments of their own, as a matter of national sovereignty they may not be able to bind the legislative competence of the State into the future. These concerns are the main driver behind this article, which is influenced by the various questions asked by policymakers in the Global South on the importance of stabilization clauses for the sustainable development and management of natural resources.